This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Assume α = 0 for simplicity. Then, the expression becomes:
Since you can replace s i n ( θ ) with c o s ( θ ) , s i n ( θ ) = c o s ( θ ) so θ = 4 5 degrees. Then, substitute 4 5 degrees for θ and 0 for α into one of the equal expressions in the problem to get m = − 2 . Since we assumed α = 0 , c o s ( α ) = 1 so the answer is ( − 2 ) 2 − 2 ( 1 ) = 2 which is the final answer.